On-Chip TaOx-Based Non-volatile Resistive Memory for in vitro Neurointerfaces - Zhuk, Maksim; Zarubin, Sergei; Karateev, Igor; Matveyev, Yury; Gornev, Evgeny; Krasnikov, Gennady; Negrov, Dmitiry; Zenkevich, Andrei (Frontiers in Neuroscience, 2020)
The development of highly integrated electrophysiological devices working in direct contact with living neuron tissue opens new exciting prospects in fields of neurophysiology and medicine, but impose tight requirements on the power dissipated by electronics. On-chip pre-processing of neuronal signals can substantially decrease the power dissipated by external data interfaces and the addition of embedded non-volatile memory would significantly improve the performance of a co-processor in real-time processing of the incoming information stream from the neuron tissue. Here, we evaluate the parameters of TaOx based resistive switching (RS) memory devices produced by magnetron sputtering technique and integrated with the 180 nm CMOS field-effect transistors as possible candidate for on-chip memory in the hybrid neurointerface under development. The electrical parameters of the optimized 1T-1R devices, such as the switching voltage ( ±1 V), the uniformity of Roff/Ron ratio ( 10), read/write speed (<40 ns) and the number of the writing cycles ( 1010), are satisfactory, however, the energy per switching cycle 100 pJ is still far too high for desired applications. Challenges arising in the course of the prospective fabrication of the proposed TaOx based RS devices in the back-end-of-line process are identified.